The problems associated with the integration of Traditional Thai Medicine (TTM) in public health policy - Senachai, Prarawan (Opción, 1970)
In 2011, Traditional Thai Medicine (TTM) was integrated into Thailand’s national healthcare policy with an established minimum target for use at 5%. After making concerted efforts, the government still has not met this target. The literature suggests that the benefits received from using TTM have not been well-recognized in Thailand, causing adoption to be unsuccessful. Clearly, the policies and practices surrounding TTM have not yet been systematically investigated in the existing health-based research, which has focused on the simple measures of consumption and access. This qualitative study aims to explain the current problems facing TTM, which are related to TTM policies and practices in Thailand and aims to explore two distinct areas: 1) current problems facing TTM (how it is being used in the public healthcare system by Thai healthcare professionals) and 2) how to support better promotion for TTM. In this study, 15 in-depth interviews with healthcare professionals across the public and private sectors were conducted on the subject of TTM policies and practices. By examining the aspects of the informants’ experiences and drawing upon the Diffusion of Innovation (DoI) framework to reveal the overarching themes, which were expressed by all of informants, the collected data was able to be used to identify a thematic map. With respect to the integration of TTM into public healthcare, the findings indicated that inconsistencies had, in fact, existed between policies and practices of those making the regulations versus the healthcare professionals in their roles as supporters. The major conflicts were as follows: 1) biases towards TTM by the policy makers; 2) a limitation of knowledge & attitude towards TTM & TTM doctors by medical doctors; 3) a conflict of work flow inside and outside of the Ministry of Public Health (MoPH); 4) legal obstacles, which had been impeding the development of TTM; and 5) a budgetary deficit, which meant that funds were not available to support TTM when attempting to integrate TTM into public healthcare policies in Thailand.